Management and outcome of community acquired pneumonia: hospital based study - Lamb, Avinash; Patil, Amol Harinathrao (International Journal of Research in Medical Sciences, 2018)
Background: Lower Respiratory Tract infections are responsible for one-fifth of the deaths caused due to infectious diseases in India and Pneumonia is a major culprit. Timely and appropriate empirical treatment based on knowledge of local etiological factors is important in the management of the disease. Data related to investigation profile and therapy as well as morbidity and mortality is available from different geographic regions. Present study describes the management and outcome of disease data from a tertiary hospital at Rajkot in Gujarat state during the study period. Methods: The present prospective observational study was completed in the study duration (November 2014 to April 2016) at tuberculosis and chest diseases Department of PDU Hospital at Rajkot, Gujarat. 50 patients above 12 years of age with CAP on clinical diagnosis assisted by radiology were included in the study. The haematology profile, therapy, complications and mortality were described. Results: Haemoglobin was below 10gm percent in 22% cases. Leucocytosis was observed in 72% cases. Ten percent patients were seropositive for HIV. There was a moderate response to treatment with penicillin group of drugs (approximately 22%). Many patients had to be offered other group of drugs like Cephalosporins, macrolides and quinolones for clinical response. Most common complications observed were: Delayed resolution in 12 (24%) patients, synpneumonic effusion in 6 (12%) and septicaemia in 3 (6%) patients. Mortality rate was 6% during the study period. Conclusions: The results indicate a low response to treatment by penicillin group antibiotics and a high rate of complications. Mortality is similar to reports from India.